Modifikasi Biopori sebagai Optimalisasi Laju Infiltrasi Air Hujan dan Dampak bagi Pengomposan Bahan Organik - Subagiyono, Subagiyono; Febriani, Heni (Jurnal Kesehatan Lingkungan Mandiri, 2023)
Accelerated development. housing on hard land, expanding house plots, filling in new land from wetlands, and changing residences into shops or offices. This causes a decrease in the capacity and carrying capacity of the environment on the earth's surface. The aim of this research is to determine the type of organic material in the biopore media which has a significant influence on the rate of water infiltration into the soil. The type of research is Quasi-experimental, with a post test only design using the Experimental Perspective Cohort method. Observations were carried out repeatedly according to the time required during the organic material degradation process in the biopores then analyzed using the true triangle experiment, namely by analyzing the components in the modified biopore media. The data that has been collected in this research is then analyzed using quantitative descriptive analysis by describing the data through the Oneway Anova Variance Test with a degree of confidence of 0.05. The research results show that the modified biopori instrument with organic vegetable material in it can maintain the rate of water infiltration into the soil. The fastest average rate of water infiltration into the soil was found in the modified biopore instrument with vegetable organic material, namely 191.16 mm/minute. The results of analysis on organic materials show teak leaves with a value of sig.0.011, vegetables with a value of sig. 0.022, straw obtained a sig value. 0.002, and paper with a sig value. 0.111. The type of vegetable organic material in the modified biopore instrument is more effective and faster in returning the rate of water infiltration into the soil to normal.